Adjacent Consonants and the Universality of Sonority Sequencing Principle in Dotyali Dialects: Syllable Contact Analysis - Dharm Dev Bhatta (Yayasan Karinosseff Muda Indonesia, 2021)
This paper presents on all the possible adjacent consonant letters in Dotyali, one of the descendant language of Sanskrit, mainly spoken in Shudoor Paschim Nepal [sʊdʊrə-pəssɪmə] (Far-western) and compares the results of their phonological changes in seven local contemporary speech (dialects)：Doteli，Dadeldhuri，Bajhangi，Achhami，Baitadeli，Darchuli and Bajureli. Based on the corpus data from the field survey conducted in between July-September 2017 on a list of 1000 frequently used Dotyali words, this paper comes with a conclusion that even the onset clusters with rising sonority profile (except glides) are broken up by vowel epenthesis or simplify the clusters by deletion. It is revealed that dialects, except from the Achhami and Bajureli, the consonants with different degree of sonority across the syllable boundary tend to be changed due to syllable contact to meet Sonority hierchy, but the sonority distance between two consonants (coda and onset consonants) varies, therefore phonological changes like assimilation, dissimilation, desonorization, contact anaptyxis, contact methasis etc. goes differently. The phonological changes in Bajureli occurs maily due to other separate independent constraints.